Optic coherence tomography findings in relapsing-remitting multiple sclerosis patients of the northwest of Iran - Talebi, Mahnaz (Tehran University of Medical Sciences, 2013)
BACKGROUND: Optical coherence tomography (OCT) is a simple, high-resolution technique to quantify the thickness of retinal nerve fiber layer (RNFL) and macula volume, which provide an indirect measurement of axonal damage in multiple sclerosis (MS). This study aimed to evaluate OCT finding in relapsing-remitting MS patients of the northwest of Iran and compare them with a normal control group. METHODS: In a cross-sectional, descriptive, analytic study, 60 patients with MS as case group and 60 patients as controls were studied. Total macular volume (TMV) and retinal nerve fiber layer (RNFL) in perioptic disk area (3.4 millimeter around the disk) and macula was measured using Stratus 3000 in circular form. These findings were compared between the two groups and their relationship with the duration and severity of MS [based on Expanded Disability Status Scale (EDSS)] and history of optic neuritis were evaluated. RESULTS: In total, 35 men and 85 women with a mean age of 34.8 years were evaluated. The mean RNFL in MS patients were 231.9 and 233.1 micrometers in right and left eyes; while they were 246.7 and 250.4 micrometers in right and left eyes of healthy subjects, respectively. This difference in thickness of RNFL in total measure and all quadrants around the optic disk and TMV between case and control groups was analytically meaningful (P = 0.001 and P = 0.001 for right and left eyes, respectively). The mean thickness of RNFL in patients with optic neuritis was significantly lower than other patients in right and left eyes (P = 0.042 and P = 0.005). There was a significant correlation between most of OCT findings and the MS disease duration and EDSS. CONCLUSION: Findings of the present study in the northwest of Iran buttress the idea that RNFL thickness can be greatly affected by MS. Our results also indicate that this effect is associated with ON and MS duration and severity.